Sociological Analysis of Islamic Law on the Relationship between Adat Law, Ethics, and Human Rights in the Context of Modern Indonesia - Nashih, Muhammad Madehin (Law and Judicial Review, 2025)
Objective: This study aims to analyze the complex relationship between Islamic law, adat law, ethics, and human rights in contemporary Indonesia, focusing on how these legal and moral systems interact in a multicultural society influenced by colonial heritage and political transformation. Research Design & Methods: This study adopts a sociological approach to legal analysis, examining historical developments, political reforms, and interactions between formal legal frameworks and everyday practices. Secondary data from scientific works, legal documents, and policy frameworks are used to provide a comprehensive understanding of Indonesia's pluralistic legal landscape. Findings: These findings reveal that the interaction between Islamic law and adat law demonstrates a process of mutual adaptation that contributes to the construction of social norms. At the same time, the integration of international and national human rights principles presents additional complexities as Indonesia seeks to harmonize universal standards with its own legal and moral foundations. Implications & Recommendations: This study underscores the need to integrate sociological perspectives into the legal reform process in Indonesia. Policymakers must consider the formal legal system and how the community understands, accepts, and practices the law to ensure that legal reform is inclusive, culturally sensitive, and sustainable. Contribution & Value Added: This study contributes to the discourse on legal pluralism by highlighting Indonesia's adaptive capacity in managing the coexistence of diverse legal traditions and ethical frameworks. It adds value by bridging theoretical insights with practical implications for legal and social reform in a multicultural context.